STRATEGI KOMUNIKASI DAKWAH RADIO GLORIA PARAMITA 97.4 FM PADA ACARA DIALOG ISLAMI - Subahri, Bambang (Institut Agama Islam Syarifuddin Lumajang, 2018)
Da'wah through radio has its own challenges in this increasingly advanced digital era. Hence, the special strategy and management are needed in maintaining the programs existence to carry out Islamic Da'wah as being performed by Islamic Dialogue on Gloria Paramita 97.4 FM Radio. This study uses a qualitative approach.  The conclusion illustrates that the communication strategy utilizes canalizing method and the form of content applies persuasive approaches and informative approaches.